Ziphius cavirostris G. Cuvier 1823 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Ziphius cavirostris G. Cuvier, 1823 —Cuvier’s Beaked Whale, goose-beaked whale Ziphius cavirostris G. Cuvier, 1823 p.350; Type locality- France; Kim et al. , 2000 p.78; Kim, 2004 p.234. Z. grebnitzkii Stejneger, 1883 p.77; Type locality- Commander Islands, Bering Sea, Russia. Range: No official records verified strandings or by-catch of Cuvier’s beaked whales from the waters of Korea. However, molecular investigations confirmed that the meat of Z . cavirostris was sold at markets in Korea (Dalebout et al . 2005). Since a federal law in South Korea prohibits the import of whale meat from other countries or deep-sea fisheries, there is high probability that the meet of Z. cavirostris in markets was poached from Korean waters (Fig. 85). Remarks: Despite regional variation in morphology (Dalebout et al. 2005), Z . cavirostris is considered a monotypic species. Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 129, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198